2018
DOI: 10.5194/cp-2018-161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blocking induced by the strengthened Siberian High led to drying in west Asia during the 4.2 ka BP event – a hypothesis

Abstract: Abstract. Causal explanations for the 4.2 ka BP event are based on the amalgamation of seasonal and annual records of climate variability manifest across global regions dominated by different climatic regimes. However, instrumental and paleoclimate data indicate that seasonal climate variability is not always sequential in some regions. The present study investigates the spatial manifestation of the 4.2 ka BP event during the boreal winter season in Eurasia, where climate variability is a function of the spati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Among the main approaches available to quantitatively reconstruct past climate from pollen data, most of the selected records have been performed using the modern analogue technique (MAT) (Guiot, 1990), an "assemblage approach" frequently used in climate reconstructions. This method was successfully used for the Holocene climate reconstructions from terrestrial and marine records (e.g., Peyron et al, 2011Peyron et al, , 2017Mauri et al, 2014Mauri et al, , 2015.…”
Section: Pollen Datamentioning
confidence: 99%
“…Among the main approaches available to quantitatively reconstruct past climate from pollen data, most of the selected records have been performed using the modern analogue technique (MAT) (Guiot, 1990), an "assemblage approach" frequently used in climate reconstructions. This method was successfully used for the Holocene climate reconstructions from terrestrial and marine records (e.g., Peyron et al, 2011Peyron et al, , 2017Mauri et al, 2014Mauri et al, , 2015.…”
Section: Pollen Datamentioning
confidence: 99%
“…Discussion paper "It is interesting to note that PerÈŹoiu et al (2018) suggested that part of the drier and cold condition over Mediterranean during the 4.2 ka event was caused by the strengthening and expansion of the Siberian High, which effectively blocked the moisturecarrying westerlies and enhanced outbreaks of cold and dry winds. "…”
Section: Additional Sentence Insertedmentioning
confidence: 99%